Interaksi Sosial Antar-Etnis dan Nilai Budaya Dalam Membangun Toleransi dan Kewarganegaraan Siswa di Sekolah Multikultural - Imam Wahyudin; Iswan, Iswan; Hatapayo , Abdul Aziz (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2024)
This research examines the dynamics of social interaction between ethnic groups and the influence of cultural values ​​on the formation of attitudes of tolerance and good citizenship among students in a multicultural school environment. Using a qualitative approach, this study involved observations, in-depth interviews, and document analysis to collect data from students and teachers in several ethnically diverse schools. The research results show that positive social interactions between students of various ethnicities promote understanding and appreciation of each other's cultural values, which is an important foundation in building tolerance. Furthermore, curricular and extracurricular activities designed to celebrate diversity are important instruments in developing students' citizenship. However, research also reveals barriers, such as prejudice and stereotypes, that need to be overcome through effective pedagogical approaches. Recommendations include developing inclusive learning programs, training teachers to manage diversity in the classroom, and integrating best practices between schools. This research provides insight into the importance of multicultural education in creating a harmonious society in the context of rich ethnic diversity.